Pete the cat. Five little pumpkins - Dean, James, 1957- (Pete the cat., 2015)
Pete the Cat takes on the classic favorite children's song "Five Little Pumpkins" in New York Times bestselling author James Dean's Pete the Cat: Five Little Pumpkins. Join Pete as he rocks out to this cool adaptation of the classic Halloween song!